The motto diplomacy respects ho chi Minh's peace and the application of Vietnam's foreign policy - Quoc Dung, Mai (Edelweiss Applied Science and Technology, 2024)
Ho Chi Minh's thought on foreign affairs, methods, style and art of diplomacy is a part of Ho Chi Minh's thought in general on Vietnam's revolutionary line. In the past time, Vietnam has strongly implemented diplomatic work according to Ho Chi Minh's diplomatic thought and achieved great successes: Vietnam's foreign relations expanded and Vietnam's position in the international arena. One of the success factors of Vietnam's diplomacy in recent years is that Vietnam has returned to Ho Chi Minh's diplomatic thought. With the promotion of participation in ASEAN, ASEM, APEC... and especially becoming a member of the World Trade Organization, Vietnam has been integrating wider and deeper into the world and the region. Many new problems arise for Vietnamese land and for Vietnamese diplomacy, both in terms of opportunities and challenges. That situation requires Vietnam to continue to study more deeply about Ho Chi Minh's foreign policy, methods, style and art, find new explanations and especially the application of Ho Chi Minh's thought.